PENERAPAN BLENDED LEARNING BERBASIS GOOGLE CLASSROOM UNTUK MENINGKATKAN KEMANDIRIAN DAN PRESTASI BELAJAR (Pada Mata Pelajaran Sejarah Indonesia Siswa kelas X di SMA Negeri 1 Pagaralam) - Metty Hana (UNIB Press, 2021)
This study aims to (1) describe the application of Blended Learning to increase the independence of Indonesian history learning for students in SMA Negeri 1 Pagar Alam; (2) Describing the application of Blended Learning to improve students' learning achievement of Indonesian History at SMA Negeri 1 Pagar Alam; (3) Describe the effectiveness of the application of Blended Learning in order to improve student achievement at SMA Negeri 1 Pagar Alam. The research was conducted using classroom action research (PTK) and quasi-experimental. The data collection method in this study used observation sheets to measure the learning process and students' learning independence and to measure learning achievement used tests. While the data analysis used analysis of the average score and test-test. The research was conducted in class X IPS 1 as the PTK class. This study resulted in the following conclusions: (1) the application of theblended learning can increase students' learning independence, (2) the application of theblended learning can improve student achievement, (3) the application of the can blended learning effectively improve student achievement in the Indonesian History subject